Draft Annual Plan Rajasthan 1989-90 Volume I - Planning Commission (Planning Commission, 1989)
Rajasthan is the second largest State in the country accounting for 10% of its area. of this, about 2/3rd of the area, covering 11 districts and habituating almost 40% of the population lies in the Thar desert. As per the 1981 Census,, the density of population stood at 100 against the national average of 216 persons per sq.km.
Planning Department, Government of Rajasthan